Highly Elastic and Self‐Healing Composite Colloidal Gels - Diba, Mani; Wang, Huanan; Kodger, Thomas E.; Parsa, Shima; Leeuwenburgh, Sander C. G. (Advanced materials (Weinheim), 2017)
Composite colloidal gels are formed by the pH‐induced electrostatic assembly of silica and gelatin nanoparticles. These injectable and moldable colloidal gels are able to withstand substantial compressive and tensile loads, and exhibit a remarkable self‐healing efficiency. This study provides new, critical insight into the structural and mechanical properties of composite colloidal gels and opens up new avenues for practical application of colloidal gels.